2021
DOI: 10.25259/sni_42_2021
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cerebrospinal fluid leak after a retrosigmoid approach for cerebellopontine angle surgery

Abstract: Background: The retrosigmoid approach represents a crucial surgical route to address different lesions in the cerebellopontine angle but cerebrospinal fluid (CSF) leak still remains the most frequent complication after this approach. Here, we analyzed the impact of different factors in CSF leak development after a retrosigmoid approach. Identifying risk factors related to a specific approach may help the surgeon to tailor the perioperative management and to appropriately counsel patients regarding their risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Full-text review of the resulting 22 articles excluded another 13 studies. The remaining nine full-text retrospective studies[ 6 , 7 , 10 , 12 , 15 , 17 , 20 - 22 ] were included in the meta-analysis [ Figure 1 ]. Please refer to Supplementary Table 2 for detailed description of individual studies including study characteristics, patient demographics, operative details, postoperative outcomes, and references.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full-text review of the resulting 22 articles excluded another 13 studies. The remaining nine full-text retrospective studies[ 6 , 7 , 10 , 12 , 15 , 17 , 20 - 22 ] were included in the meta-analysis [ Figure 1 ]. Please refer to Supplementary Table 2 for detailed description of individual studies including study characteristics, patient demographics, operative details, postoperative outcomes, and references.…”
Section: Resultsmentioning
confidence: 99%
“…This could potentially skew the result towards favoring craniotomies given their significantly lower occurrence of pseudomeningocele formation. In addition, only two studies were included in the combined outcome but not in the CSF leak comparison;[ 17 , 21 ] one of which favored craniectomies[ 21 ] causing substantial heterogeneity (I 2 = 59%). Thus, it is difficult to attribute this difference in significance to the incorporation of articles that did not differentiate between postoperative CSF leak and pseudomeningocele, which was the rationale behind including the combined outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of prophylactic LDs for CSF leak repairs remains controversial. Previous reports have shown that universal LD is not necessary for sCSF-L repair with the MCF approach in obese patients (10,11). However, the postoperative CSF leak rate in class III obese patients (body mass index [BMI] > 40) undergoing sCSF-L repair and thus the need for prophylactic LD placement in this population has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article by Montano et al . [ 1 ] on the factors associated with cerebrospinal fluid (CSF) leak after a retrosigmoid approach for cerebellopontine angle surgery. The authors have rightly pointed out that performing a craniectomy and a reopening procedure as significantly associated with a higher risk of CSF leak.…”
mentioning
confidence: 99%